Analisis kondisi tegakan pada kawasan hutan perkotaan dan pengaruhnya ter-hadap iklim mikro Di Kota Manokwari - Tri Apdian, Yulianto; H. S. Siburian, Rima; Murdjoko, Agustinus (Cassowary, 2025)
ABSTRACT: This research aims to analyze forest stand conditions that influence the microclimate in Manokwari urban forests and microclimate conditions that can provide comfort for the surrounding environment. The results of satellite imagery photos show that Manokwari city's land use is forest in the 5 year period, there has been a change in land use area, in 2017 the residential area was 1,512.34 ha to 1,714.58 Ha in 2022, there was an increase of 202.24 Ha. The temperature inside the forest area was recorded at 26.3°C, while outside the forest area it was recorded at 31.1°C. Manokwari has experienced extreme microclimate changes over the last 5 years, the temperature has increased to around 1.5°C, apart from that the humidity has also been recorded to have decreased significantly. Analysis of the comfort index shows that the forest temperature in the Amban region is lower than in other areas studied. Another important thing is that areas in the city that have stands of trees can immediately be designated as urban forests. Based on an analysis of oxygen consumption in various sectors and its population, Manokwari City requires the development of around 918.96 ha of urban forest. To maintain the continuity of the microclimate, it is necessary to immediately issue regulations by the Regional Government regarding the designation of existing areas as urban forests.